Perbandingan Algoritma Golomb Code Dengan Algoritma Punctured Elias Code Dalam Kompresi File Video - Irawati, Irawati (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2024)
In today's digital era, the use of data compression technology is very important because the utilization of data in electronic form is faster for exchanging information.Large file sizes require a lot of storage space. Video files have a large size compared to other types of video files. Because the mp4 file size is too large, the process of sending data takes a long time. One of the techniques needed for this problem is compression. Compression is the process of resizing data to a smaller size. The algorithms used in this research are the Golomb Code algorithm and the Punctured Elias Code algorithm, which have their own advantages and disadvantages. After the two algorithms are compressed, a comparison of the two algorithms is made using the exponential method. The exponential comparison method is one of the methods used to determine the priority order of alternative decisions based on several criteria. The final result of the comparison process with the exponential method obtained a result of 7.296, which is the Golomb Code algorithm. So that the algorithm becomes the fastest and most effective algorithm in compressing video files, this is because the smaller the total value obtained, the less effort made by the algorithm in compression.